Morfofonêmica e morfossintaxe do Maxakalí - Carlo Sandro de Oliveira Campos (2009)
This research describes aspects of the phonology, morphology and morphosyntax of the indigenous language Maxakalí. Based on morphological case marking, I show that the Maxakalí language has a tripartite case system whose arguments (A), (So) and (O) are each encoded differently. In addition, I demonstrate that Maxakalí's case system is ergative-active, since the (A) and (Sa) arguments are consistently marked by an ergative post-position. From a generative theoretical perspective, based on the notions of structural and inherent Case, I sought empirical reasons to show the status of absolutive and ergative cases. Using morphological, syntactic and semantic diagnostic tools, I found evidence that the absolutive case in Maxakalí is equivalent to two distinct abstract Cases: nominative and accusative. By means of syntactic and semantic tests, I present evidence that the ergative case in Maxakalí is inherent. The status of the absolutive and ergative cases in Maxakalí show that the language uses a tripartite system both morphologically and structurally speaking, as the arguments (A), (So) and (O) are distinctly marked morphologically, as well as receiving distinct abstract Cases. Based on the notions of thematic roles and argument structure (Hale e Keyser, 1994, 2002); I've classified the intransitive verbs of Maxakalí into two distinct verb classes: unaccusatives and ergatives, providing linguistic and structural motivations to support the split VP structure proposed. Regarding the phonology of the language, I described phonological processes including causative constructions, diminutive constructions and reduced nouns and verbs according to the phonotactic patterns identified. These phonological processes indicate that there are interactions between the morphological and phonological components of the Maxakalí language.